Evaluating the effectiveness of mindfulness-based interventions on rumination and negative emotions in Chinese University Students: A randomized controlled trial - Keke Shi; Guoyan Feng; Meilin Ye; Xiaoyan Bi; Hongbo Cui; Weiyu Chen; Tao Gao; Zaihua Qing; Yankun Ma (PLoS ONE, 2025)
Objectives Rumination and negative emotions are prevalent among university students and are strongly linked to mental health disorders, including depression and anxiety. Group counseling involving a mindfulness-based strategies may help prevent university students from developing rumination and negative emotions and subsequent mental health disorders. This study aims to evaluate the alleviating effect of mindfulness intervention on rumination and negative emotions in university students in China. Methods A randomized controlled trial (RCT) with 2 arms (Intervention Group and Control Group), three assessment time points (pre-intervention, post-intervention, and 3-month follow-up) is proposed. A total of 196 university students are randomly assigned to an intervention group (n = 98) receiving a 2-week, daily 1.5-hour mindfulness training (MT) and a control group (n = 98) receiving peer support (PS) sessions. Participants complete the Mindful Attention Awareness Scale (MAAS), Depression-Anxiety-Stress Scale (DASS-21), and Ruminative Responses Scale (RRS) before, immediately after, and three months post-intervention. Statistical analysis will compare outcomes between groups to evaluate the effectiveness using a repeated-measures ANOVA. Results Before the intervention, no significant differences are observed between groups. After the intervention, the MT group shows significant improvements in MAAS scores and reductions in DASS-21 scores (p < 0.05) compared to the PS group. While immediate improvements in rumination (RRS) are not significant, the MT group exhibits significant reductions in rumination three months post-intervention. Conclusion This study contributes to a better understanding of the effectiveness of mindfulness intervention in alleviating rumination and negative emotions in university students, and it is expected that with the proposed intervention university students can improve their psychological well-being. Besides, mindfulness interventions can potentially be extended to participants suffering from other psychological issues in the future.